Evaluating the heterogeneity of street life and homelessness in adolescent research. Issue 3 (24th January 2019) - Stablein, Timothy; Clark, Elyse
Abstract: Researchers of homelessness have been careful to delineate the heterogeneity of adolescent homelessness and street involvement when defining and differentiating street life experiences around the globe. Understanding these experiences poses challenges to researchers as adolescents across these locations come to the street at various stages of transition and homelessness yet share similarities. In this article, we review homeless research to understand both the heterogeneous characteristics and experiences adolescents have when they become involved in street life and homelessness around the world, as well as the similarities and differences they globally share. We review and compare general definitions of street life and homelessness presented in observations of young people on the street in the developed and developing worlds. We then explore interrelated characteristics outlined by researchers across these studies and locations, namely, the homeless status of street life participants and their socialization to street life as well as their network affiliations. Although this collected body of work reveals a complex heterogeneity of street involvement among all those that participate, it also shows how the young and street involved around the globe share these commonalities with one another which challenges the frameworks and classifications that guide contemporary global research among the homeless.